Parasitism of hamster trachea epithelial cells by Mycoplasma pneumoniae. - Chen, Y Y (1988)
Hamster trachea epithelial (HTE) cells were employed as a model system for Mycoplasma pneumoniae pathogenesis. To more closely mimic natural infection, M. pneumoniae was forced to rely upon host cells (as opposed to the growth medium) for nutrients, and infections were initiated with relatively low mycoplasma doses and monitored for extended time periods. A time- and dose-dependent decline in the viability of infected cells was observed; however, viability never declined below 50% of that in uninfected controls. Protein and RNA synthesis actually increased above control levels in infected cells, despite a concomitant decrease in viability. This response was pronounced at higher multiplicities of infection but was only transient at lower doses. In parallel studies in which a culture medium capable of supporting M. pneumoniae growth was used, loss of viability was accelerated. With a low-dose infection a transient increase followed by a precipitous decline in macromolecular synthesis was observed, relative to that in uninfected controls. At higher doses, however, macromolecular synthesis decreased dramatically and in proportion to the loss of viability. The requirement for HTE cells for mycoplasma growth under the experimental culture conditions was demonstrated by quantitating viable mycoplasmas in the culture medium in the presence or absence of HTE cells over 4 days. The increase in mycoplasma number was negligible in the absence of HTE cells, while a 30-fold increase was observed in the presence of HTE cells. These findings demonstrate the feasibility of long-term, low-dose studies of M. pneumoniae pathogenesis with trachea epithelial cells and a nonpermissive culture medium. This experimental system should facilitate the elucidation of the mechanism(s) responsible for host cell injury, and perhaps reveal how host cells respond to infection.